Prognostic Value of the Distribution of Lymph Node Metastasis in Locally Advanced Rectal Cancer After Neoadjuvant Chemoradiotherapy - Chen, Bin; Liu, Xing; Zhang, Yiyi; Zhuang, Jinfu; Peng, Yong; Wang, Ye; Wu, Yong; Li, Shoufeng; Yang, Yuanfeng; Guan, Guoxian (Frontiers in Surgery, 2021)
Background: The objective of this study is to assess the prognostic value of lymph node metastasis distribution (LND) in locally advanced rectal cancer (LARC) after neoadjuvant chemoradiotherapy (nCRT). Methods: This study included 179 patients with pathological stage III LARC who underwent nCRT followed by radical surgery. LND was classified into three groups: LND1, lymph node metastasis at the mesorectum (140/179, 78.2 %); LND2, lymph node metastasis along the inferior mesenteric artery trunk nodes (26/179, 14.5 %); LND3, lymph node metastasis at the origin of the IMA (13/179, 7.3 %). Clinicopathologic characteristics were analyzed to identify independent prognostic factors. Result: LND showed better stratification for 3-year DFS (LND1 66.8 %, LND2 50 %, and LND3 15.4 %, P < 0.01) compared to the ypN (3-year DFS: N1 59.9 % and N2 60.3 %, P = 0.34) and ypTNM (3-year DFS: IIIA 68.6 %, IIIB 57.5%, and IIIC 53.5, P = 0.19) staging systems. Similar results were found for 3-year LRFS and DMFS. According to multivariate survival analysis, LND was shown to be an independent prognostic factor for DFS, LRFS, and DMFS in patients with positive lymph nodes (P < 0.01, in all cases). Conclusion: LND is an independent prognostic factor in stage III rectal cancer after nCRT. LND can be used as a supplementary indicator for the ypTNM staging system in patients with LARC after nCRT.